Dampak Pandemi Terhadap Penyerapan Anggaran di Kantor Kementerian Agama Kabupaten Mojokerto - Andik Suyitno (Jurnal Public Policy, 2020)
The government made a lot of efforts in preventing the spread of Covid-19, this greatly affected for the realization of budget absorption especially on employee expenditure, goods expenditure and capital expenditure. By taking secondary data from expenditure realization in 2019 and expenditure realization data from 2020 to June, the effects of the spread of Covid-19 on budget absorption can be seen, especially at the Mojokerto Regency Ministry of Religion Office. From the results of the efficiency ratio found an increase in the category of sufficient efficiency to be very efficient, but the value of budget absorption to the maximum compliance of absorption every quarter found a decrease from the very good value category to the bad value category. There is a positive impact on the budget for the coming year, namely in terms of budget savings and efficient use of the budget. With lower costs (decreasing) agency services to the community continue to be carried out to the maximum and the same output is achieved.